2019
DOI: 10.1126/science.aav4011
|View full text |Cite
|
Sign up to set email alerts
|

VDAC oligomers form mitochondrial pores to release mtDNA fragments and promote lupus-like disease

Abstract: Mitochondrial stress releases mitochondrial DNA (mtDNA) into the cytosol, thereby triggering the type Ι interferon (IFN) response. Mitochondrial outer membrane permeabilization, which is required for mtDNA release, has been extensively studied in apoptotic cells, but little is known about its role in live cells. We found that oxidatively stressed mitochondria release short mtDNA fragments via pores formed by the voltage-dependent anion channel (VDAC) oligomers in the mitochondrial outer membrane. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
446
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 457 publications
(458 citation statements)
references
References 35 publications
10
446
0
2
Order By: Relevance
“…Although the involvement of VDACs in the formation of the permeability transition pore has been debated ( 35 ), studies also indicate that adverse changes in the lipid profile of the OMM could trigger the observed VDAC oligomerization and release of mitochondrial DNA ( 36 ). The most significant change in the lipidome is the lowering of CL and a concomitant increase in PG content ( 23 , 27 , 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the involvement of VDACs in the formation of the permeability transition pore has been debated ( 35 ), studies also indicate that adverse changes in the lipid profile of the OMM could trigger the observed VDAC oligomerization and release of mitochondrial DNA ( 36 ). The most significant change in the lipidome is the lowering of CL and a concomitant increase in PG content ( 23 , 27 , 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is possibly due to mtDNA release, though a direct role for mtDNA has not been rigorously assessed . An intriguing recent report suggests that cells experiencing mitochondrial stress caused by the lack of mitochondrial endonuclease G release mtDNA through pores formed by oligomers of the voltage‐dependent anion channel (VDAC) . As mitochondrial DNA release is thought to play a role in the pathogenesis of lupus , a role for VDAC pore formation was tested in an in vivo model of lupus‐like disease.…”
Section: Introductionmentioning
confidence: 99%
“…As mitochondrial DNA release is thought to play a role in the pathogenesis of lupus , a role for VDAC pore formation was tested in an in vivo model of lupus‐like disease. Using the VDAC1 oligomerisation inhibitor VBIT‐4, the authors were able to reduce lupus‐like symptoms in lupus‐prone mice, providing a rationale to target VDAC‐mediated mtDNA release in this disease .…”
Section: Introductionmentioning
confidence: 99%
“…The protein is also involved in cholesterol transport and mediates the fluxes of ions, including cytosolic and Ca 2+ , as well as being involved in mitochondria-ER Ca 2+ signaling, serving as a ROS transporter, and regulating the redox states of mitochondria and the cytosol [40,42]. Furthermore, recently we demonstrated that VDAC1 oligomers mediate the release of mitochondrial DNA fragments [43]. Thus, VDAC1 appears to be a convergence point for a variety of cell survival and death signals, mediated through association with various ligands and proteins [40,42].The importance of VDAC1 in cell energy and metabolism homeostasis is reflected in its over-expression in many cancers [44,45], and with down-regulation resulting in reduced metabolite exchange between mitochondria and cytosol and inhibited cell and tumor growth [44,[46][47][48].…”
mentioning
confidence: 99%
“…The protein is also involved in cholesterol transport and mediates the fluxes of ions, including cytosolic and Ca 2+ , as well as being involved in mitochondria-ER Ca 2+ signaling, serving as a ROS transporter, and regulating the redox states of mitochondria and the cytosol [40,42]. Furthermore, recently we demonstrated that VDAC1 oligomers mediate the release of mitochondrial DNA fragments [43]. Thus, VDAC1 appears to be a convergence point for a variety of cell survival and death signals, mediated through association with various ligands and proteins [40,42].…”
mentioning
confidence: 99%